MoS2@ZnO Nanoheterostructures Prepared by Electrospark Erosion for Photocatalytic Applications; Nanomaterials; Vol. 11, iss. 1 - An V. V. Vladimir Vilorievich; Potgieter J. H. Johannes Herman; Usoltseva N. V. Natalia Vasilievna; Valiev D. T. Damir Talgatovich; Stepanov S. A. Sergey Aleksandrovich; Pustovalov A. V. Aleksey Vitalievich; Baryshnikov A. A. Arseny Aleksandrovich; Titov M. N. Maksim Nikolaevich; Dolinina A. S. Alesya Sergeevna (2021, 2021)
Title screen